Effects of Sleep Quality on Cardiovascular System, Anxiety, And Academic Performance in Medical and Dental Students in Peshawar, Pakistan - Asia, Shahid Waseem, Marina Hidayat, Robina Usman, Memona Haq, Zainu Abedeen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Sleep disturbance is an important issue among medical students and high stress including the pressure of maintaining grades might affect the quality of sleep among students. Objective: To determine the effects of sleep quality on medical and dental students’ cardiovascular system, academic performance, and anxiety at Peshawar Medical and Dental College. Methodology: The Riphah International University and Prime Foundation Pakistan Institutional Review Board approved a cross-sectional research for their respective institutions. Interrogation of randomly chosen individuals was conducted using the Pittsburgh Sleep Quality Index (PSQI), as well as physiological data. The data were entered and analyzed using SPSS-25. Result: In our research, out of 600 individuals, 286 (46.7%) had excellent sleep quality (PSQI score less than 5) and 314 (52.3%) had poor sleep quality (PSQI score larger than 5). (PSQI score greater than 5). Among medical students, there was a statistically significant link between sleep quality and physiologic parameters, academic performance, and anxiety score; heart rate (p0.05), systolic blood pressure (p0.05), diastolic blood pressure (p0.01), and academic performance (p0.05) were all linked. Conclusion: Academic performance, heart rate, and blood pressure were shown to be significantly correlated with sleep quality in dentistry and medical students; however sleep quality was not found to be significantly correlated with anxiety scores. Keywords: Effects, Sleep Quality, Cardiovascular System, Anxiety, Academic Performance